To flare or not to flare: patients’ and rheumatologists’ perceptions on the on-flare retreatment strategy of rituximab in rheumatoid arthritis - Delphine Bertrand; Anke Deprez; Michaël Doumen; Diederik De Cock; Sofia Pazmino; Anja Marchal; Marc Thelissen; Johan Joly; Elias De Meyst; Barbara Neerinckx; René Westhovens; Patrick Verschueren (Therapeutic Advances in Musculoskeletal Disease, 2024)
Background: Several retreatment strategies exist for rituximab in rheumatoid arthritis (RA). In some countries, reimbursement criteria require a loss of disease control for rituximab retreatment. Understanding the patients’ and rheumatologists’ perceptions regarding this retreatment strategy would be informative in identifying the optimal treatment administration schedule. Objectives: This study aimed to uncover patients’ and rheumatologists’ perceptions regarding retreatment strategies of rituximab. Design: Qualitative study – semi-structured interviews Methods: Patients with RA, treated with rituximab, and rheumatologists were invited to participate in a qualitative study consisting of individual, in-depth, semi-structured interviews. Interviews were analysed according to the Qualitative Analysis Guide of Leuven. Results: A total of 16 patients and 13 rheumatologists were interviewed. Benefits (e.g. decreased risk of overtreatment, cost savings and long-lasting effectiveness of rituximab) and barriers (e.g. fluctuating disease activity, slow mode of action and increased glucocorticoid use) of on-flare retreatment were identified. To effectively treat on-flare, flares must first be identified timely. Both stakeholder groups acknowledged that patients are capable of recognizing flares. However, the patient’s ability to discriminate between inflammatory and other types of pain was perceived as difficult. Furthermore, patients and rheumatologists stressed that patients must timely seek professional help in case of a flare, followed by a swift response from the rheumatologists. Remarkably, retreatment was approached in various ways among rheumatologists, and not always adhering strictly to the on-flare reimbursement criteria. Conclusion: This study revealed that both stakeholder groups perceived the heterogeneity in recognition of and reaction to a flare as important in influencing the effectiveness of the on-flare retreatment strategy. Moreover, this study identified the benefits and barriers of treating on-flare, which could be informative for daily practice decisions.